Co-expression Patterns between ATN1 and ATXN2 Coincide with Brain Regions Affected in Huntington’s Disease - Keo, Arlin; Aziz, N. Ahmad; Dzyubachyk, Oleh; van der Grond, Jeroen; van Roon-Mom, Willeke M. C.; Lelieveldt, Boudewijn P. F.; Reinders, Marcel J. T.; Mahfouz, Ahmed (Frontiers in Molecular Neuroscience, 2017)
CAG Repeat expansions in the coding regions of nine polyglutamine (polyQ) genes (HTT, ATXN1, ATXN2, ATXN3, CACNA1A, ATXN7, ATN1, AR, and TBP) are the cause of several neurodegenerative diseases including Huntington's disease (HD), six different spinocerebellar ataxias (SCAs), dentatorubral-pallidoluysian atrophy and spinobulbar muscular atrophy. The expanded CAG repeat length in the causative gene is negatively related to the age-at-onset (AAO) of clinical symptoms. In addition to the expanded CAG repeat length in the causative gene, the normal CAG repeats in the other polyQ genes can affect the AAO, suggesting functional interactions between the polyQ genes. However, there is no detailed assessment of the relationships among polyQ genes in pathologically relevant brain regions. We used gene co-expression analysis to study the functional relationships among polyQ genes in different brain regions using the Allen Human Brain Atlas (AHBA), a spatial map of gene expression in the healthy brain. We constructed co-expression networks for seven anatomical brain structures as well as a region showing a specific pattern of atrophy in HD patients detected by magnetic resonance imaging (MRI) of the brain. In this HD-associated region, we found that ATN1 and ATXN2 were co-expressed and shared co-expression partners which were enriched for DNA repair genes. We observed a similar co-expression pattern in the frontal lobe, parietal lobe, and striatum in which this relation was most pronounced. Given that the co-expression patterns for these anatomical structures were similar to those for the HD-associated region, our results suggests that their disruption is likely to be involved in HD pathology. Moreover, across the brain, ATN1 and ATXN2 also shared many co-expressed genes with HTT, the causative gene of HD. Although this triangular relationship among these three polyQ genes may also be dysregulated in other polyQ diseases, stronger co-expression patterns between ATN1 and ATXN2 observed in the HD-associated region, especially in the striatum, may be more specific to HD.